Psychotherapeutic approaches: hopefully, globally effective - Howe, Edmund (Frontiers in Psychiatry, 2024)
Many patients have lasting disorders due, for example, to excessive and chronic childhood stress. For these patients, certain psychotherapeutic approaches may be maximally effective, and this may be universally the case. This piece is intended to give providers optimal tools for reaching and helping these patients who, otherwise, may remain among those worst off. These interventions should enhance patients’ trust, the quintessential precondition for enabling these patients to change. Specific interventions discussed include anticipating ambiguity and clarifying this before ambiguity occurs, therapists indicating that they will support patients’ and families’ wants over their own views, feeling and disclosing their emotions, validating patients’ anger, laughing, going beyond usual limits, explaining why, asking before doing, discussing religion and ethics, and informing whenever this could be beneficial.